LITERATURE STUDY: THE PROBLEMATICS IN APPLICATING COOPERATIVE LEARNING MODEL TYPE TEAMS GAMES TOURNAMENTS (TGT) AND ALTERNATIVE COMPLETION - Farah Dzil Barr (Universitas Muhammadiyah Semarang, 2018)
Various learning models have been applied in teaching and learning activities. However in the practice there are some problems in its application. One of them is cooperative learning model type Teams Games Tournaments (TGT). This research uses literature study method and analysis of various problems of application of cooperative model of TGT type and its solution alternative. The result of this research is step modification / procedure of TGT learning model in the more effective and efficient time.Keywords: Cooperative Learning, TGT Model